Synaptotagmin-7, a binding protein of P53, inhibits the senescence and promotes the tumorigenicity of lung cancer cells. Issue 2 (8th February 2019) - Fei, Zhenhua; Gao, Wei; Xie, Raoying; Feng, Ganzhu; Chen, Xiaolin; Jiang, Yiyan
Abstract : Lung cancer has been one of the most common malignancies in the world. Cell senescence has been recognized as the avenue to inhibit tumor progression. However, the mechanisms remain poorly understood. In the present study, we have shown that synaptotagmin-7 (SYT7) expression was up-regulated in lung cancer. SYT7 also promoted the growth and colony formation of lung cancer cells and inhibited their senescence. In a molecular mechanism study, SYT7 was shown to interact with P53 and to potentiate the interaction between P53 and MDM2. Taken together, the present study demonstrates the oncogenic roles of SYT7 in lung cancer, and suggests that SYT7 may be a good therapeutic target for lung cancer treatment.